Diagnostic value and correlation analysis of serum cytokine levels in patients with multiple system atrophy - Chen, Xueping; Chen, Sihui; Lai, Xiaohui; Fu, Jiajia; Yang, Jing; Ou, Ruwei; Zhang, Lingyu; Wei, Qianqian; Guo, Xiaoyan; Shang, Huifang (Frontiers in Cellular Neuroscience, 2024)
The association between cytokines in peripheral blood and clinical symptoms of multiple system atrophy (MSA) has been explored in only a few studies with small sample size, and the results were obviously controversial. Otherwise, no studies have explored the diagnostic value of serum cytokines in MSA.: Serum cytokines, including interleukin-6 (IL-6), interleukin-8 (IL-8), and tumor necrosis factor alpha (TNF-α), were measured in 125 MSA patients and 98 healthy controls (HCs). Correlations of these serum cytokines with clinical variables were analyzed in MSA patients. Diagnostic value of cytokines for MSA was plotted by receiver operating curves.Results: No significant differences were found in sex and age between the MSA group and the HCs. TNF-α in MSA patients were significantly higher than those in HCs (area under the curve (AUC) 0.768), while IL-6 and IL-8 were not. Only Hamilton Anxiety Scale (HAMA) has a positive correlation between with TNF-α in MSA patients with age and age at onset as covariates. Serum IL-6 was associated with HAMA, Hamilton Depression Scale (HAMD), the Unified MSA Rating Scale I (UMSARS I) scores, the UMSARS Ⅳ and the Instrumental Activity of Daily Living scores. However, IL-8 was not associated with all clinical variables in MSA patients. Regression analysis showed that HAMA and age at onset were significantly associated with TNF-α, and only HAMA was mild related with IL-6 levels in MSA patients.Serum TNF-α and IL-6 levels in MSA patients may be associated with anxiety symptom; however, only TNF-α was shown to be a useful tool in distinguishing between MSA and HCs.